Legal Legitimacy and Effectiveness of the KMPMDP Program in Preventing Maladministration Through Policy Cycle - Roshe Adeltha Hendri; Jatmiko Yogopriyatno; Nursanty Nursanty (Rechtenstudent, 2026)
This study analyzes the implementation of the Community Group Concerned with Maladministration (KMPMDP) program conducted by the Ombudsman of the Republic of Indonesia Bengkulu Representative using Jann and Wegrich's (2007) Policy Cycle Theory integrated with Administrative Law perspectives. The KMPMDP program represents a strategic innovation in public service oversight based on community participation that implements principles of administrative democratization and governmental accountability. Using a qualitative approach with an interpretive paradigm, this research examines how the program is implemented through five policy cycle stages while considering dimensions of legality, legitimacy, and general principles of good governance (AUPB). Data were collected through in-depth interviews with key actors, participatory observation of program activities, and documentary studies. Findings reveal that the KMPMDP program has a strong legal foundation based on Law No. 37/2008 on the Ombudsman RI and fulfills administrative law principles at each policy cycle stage. However, implementation faces technical constraints, particularly in edu-visit coordination, impacting effectiveness and efficiency as part of AUPB. The study shows a gap between formal rechtmatigheid (legal validity) and substantive doelmatigheid (effectiveness), with only 50% of planned edu-visits executed. This research contributes theoretically to participatory policy implementation studies from an administrative law perspective and provides practical recommendations for optimizing legitimate and accountable community-based oversight programs.